Pharmacokinetic characterization of baclofen in patients with chronic kidney disease: dose adjustment recommendations. (10th January 2014) - Vlavonou, Raphaël; Perreault, Marc M.; Barrière, Olivier; Shink, Eric; Tremblay, Pierre‐Olivier; Larouche, Richard; Pichette, Vincent; Tanguay, Mario
Abstract The pharmacokinetics of baclofen is well delineated in subjects with normal kidney function (KF); however, pharmacokinetics data in patients with chronic kidney disease (CKD) are not and dosage recommendations remain empirical. The effects of CKD on baclofen pharmacokinetics were assessed through a multi‐center, open‐label, single 5‐mg dose, pharmacokinetics study. The KF was measured as the creatinine clearance (CrCL) calculated with the Cockroft–Gault (C–G) equation or as the estimated glomerular filtration rate (eGFR) using subjects' CKD‐EPI equation. Subjects were assigned to 1 of 4 groups based on their CrCL (>80 mL/min, 50–80 mL/min; 30–50 mL/min and <30 mL/min). Cmax was not statistically different between the groups, while AUC and T1/2el increased, and CL/F decreased, with increasing severity of CKD. Baclofen's oral clearance and CrCL were statistically significantly correlated, and the trend was the same when classifying subjects either with the CKD‐EPI or C–G equations. Linear equations using KF as variable were set to recommend individual dose reduction in CKD patients. Results suggest a mean dose reduction of 1/3, 1/2, and 2/3 in patients with mild, moderate, and severe CKD respectively, in order to achieve baclofen exposure comparable to that observed in healthy subjects.